Why Should People Outside the Nordic Region Be Interested in Teacher Education in the Nordic Region? - Elstad, Eyvind (Springer International Publishing, 2023)
Abstract The Nordic region consists of five northern European countries—Norway, Sweden, Finland, Denmark and Iceland—along with their autonomous territories: Greenland, the Faroe Islands and the Åland Islands. The Sámi people also reside in the Nordic region. Large parts of the Nordic region came late to development and prosperity. However, today these countries are some of the happiest and most prosperous, egalitarian and progressive in the world. The societies of the Nordic region are among the world’s most well-organized, and their formidable economic growth is in part due to a longstanding commitment to education. Large parts of the world are looking to the Nordic countries and the Nordic model of social organization, and interest in the Nordic comprehensive school system and teacher education arrangements is no exception. The tenets of Nordic education include the development of social justice, equal opportunities for all learners, participatory democracy and inclusion, all of which foster the development of competence and align with the broader values of the Nordic welfare state. A good education is a key to prosperity and well-being. The quality of education is undoubtedly linked to the quality of teacher education.